Book Reviews. Issue 4 (1st December 2019) - Tywoniak, Ed; McCullough, Ryan P.; Strate, Lance; Anton, Corey; Maier, Craig; Bogaczyk, Jeff; Malin, Brenton J.; McCullough, Ryan P.; Cooper, Tom
Media and Formal Cause, Marshall McLuhan and Eric McLuhan (2011)Houston, TX: NeoPoiesis Press, 165 pp., ISBN 978-0-98327-470-4, p/bk, 18.95Taking Up McLuhan's Cause: Perspectives on Media and Formal Causality, Corey Anton, Robert K. Logan and Lance Strate (eds) (2017)Bristol, UK and Chicago, IL: Intellect, 287 pp., ISBN 978-1-78320-694-0, h/bk, 100.00Theories of Communication, Eric McLuhan and Marshall McLuhan (2011)New York: Peter Lang, 253 pp., ISBN 978-1-43311-213-3, h/bk, 119.47, p/bk, 36.47The Human Equation: The Constant in Human Development and Culture from Pre-literacy to Post-literacy, Book 1, The Human Equation Toolkit, Wayne Constantineau and Eric McLuhan, Illustrations by Heidi Overhill (2010)Toronto and New York: BPS Books, 104 pp., ISBN 978-1-92664-534-6, p/bk, 15.00 CAD / 15.00 USDThe Science of Investigation: Working with Equations, Book 2, The Human Equation Toolkit, Wayne Constantineau and Eric McLuhan, Illustrations by Heidi Overhill (2012)Toronto and New York: BPS Books, 94 pp., ISBN 978-1-92664-534-6, p/bk, 15.00 CAD / 15.00 USDKnow Thyself: Action and Perception, Book 3, The Human Equation Toolkit, Wayne Constantineau and Eric McLuhan, Illustrations by Heidi Overhill (2012)Toronto and New York: BPS Books, 106 pp., ISBN 978-1-92748-326-8, p/bk, 15.00 CAD / 15.00 USDCynic Satire, Eric McLuhan (2015)Newcastle upon Tyne, UK: Cambridge Scholars Publishing, 250 pp., ISBN 978-1-44387-760-2, h/bk, 81.85The Sensus Communis, Synesthesia, and the Soul: An Odyssey, Eric McLuhan (2015)New York, NY: BPS Books, 142 pp., ISBN-13 978-1-77236-022-6, p/bk, 13.95, epub, 8.49The Lost Tetrads of Marshall McLuhan, Marshall McLuhan and Eric McLuhan (2017)New York, NY: OR Books, 273 pp., ISBN 978-1-68219-096-8, p/bk, 18.00Work/Text: Investigating the Man from U.N.C.L.E., Cynthia Walker (2013)New York, NY: Hampton Press, 379 pp., ISBN-13 978-1-61289-121-7, p/bk, 31.22How to Avoid Making a Fool of Yourself, R. Wayne Pace (2017)New York, NY: Institute of General Semantics, 124 pp., ISBN 978-0-98607-647-3, h/bk, 15.00Media Ethics and Global Justice in the Digital Age, Clifford G. Christians (2019)Cambridge, UK: Cambridge University Press, 409 pp., ISBN 978-1-10715-214-4, h/bk, 88.26, p/bk, 31.96, epub, 28.00